Multistage nanostructure NiTiTaMoNbW high-entropy alloy film and mechanical property regulation and control method thereof

By preparing multi-stage nanostructured NiTiTaMoNbW high-entropy alloy film and using laser annealing treatment, the problem that existing high-entropy alloy films are difficult to meet the strength and ductility requirements at the same time is solved, and a combination of high yield strength and high elastic strain is achieved.

CN119753477APending Publication Date: 2025-04-04SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411702870.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing high-entropy alloy films are difficult to meet both strength and ductility requirements.

Method used

By preparing a multi-stage nanostructured NiTiTaMoNbW high-entropy alloy film, a recrystallization layer was formed by laser annealing treatment, and the crystal phase volume ratio was adjusted to improve the yield strength and elastic strain.

Benefits of technology

The combination of high yield strength and high elastic strain is achieved, and the requirements of high strength and high ductility are met at the same time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753477A_ABST
    Figure CN119753477A_ABST
Patent Text Reader

Abstract

The invention discloses a NiTiTaMoNbW high-entropy alloy film with a multi-stage nano structure and a mechanical property regulation and control method of the NiTiTaMoNbW high-entropy alloy film. Wherein the high-entropy alloy film with the multi-stage nano structure is made of NiTiTaMoNbW alloy, and the high-entropy alloy film comprises the following components in atomic percent: 22% of Ni, 14.1% of Ti, 18% of Ta, 16.6% of Mo, 13% of Nb and 16.2% of W. According to the method, on the basis that the near-isoatomic NiTiTaMoNbW high-entropy alloy thin film is prepared, the NiTiTaMoNbW high-entropy alloy thin film is treated in a laser annealing mode, the volume percentage of a crystal phase in the NiTiTaMoNbW high-entropy alloy thin film is adjusted, and then the NiTiTaMoNbW high-entropy alloy thin film of a multi-stage nano structure is obtained; the yield strength and the elastic strain of the high-entropy alloy film are higher than those of an existing high-entropy alloy film, and the requirements for high strength and high ductility can be met at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of heterogeneous structural metal materials, and in particular to a multi-level nanostructured NiTiTaMoNbW high entropy alloy film and a method for regulating its mechanical properties. Background Art

[0002] High-entropy alloy films (HEA) are usually new alloys formed by five or more metals in equal or relative proportions. It is a new type of material with excellent performance. Due to its unique microstructure, excellent thermal stability and catalytic activity for various reactions, it has attracted widespread attention from the scientific community and has a wide range of applications in the fields of marine shipbuilding, aerospace, and energy. However, in different application scenarios, there are different requirements for the mechanical properties of high-entropy alloy films, or it is difficult to meet the requirements of strength and ductility at the same time. Therefore, the existing technology needs to be improved. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a high entropy alloy film, a method for regulating mechanical properties and a multi-level nanostructured high entropy alloy film, aiming to solve the problem that existing high entropy alloy films are difficult to simultaneously meet the requirements of strength and ductility.

[0004] The technical solution of this application is as follows:

[0005] In a first aspect of the present application, a multi-level nanostructured NiTiTaMoNbW high entropy alloy film is provided. The material of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film is a NiTiTaMoNbW alloy. The atomic percentages of the components of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film are: Ni: 10-25%, Ti: 10-25%, Ta: 10-25%, Mo: 10-25%, Nb: 10-25%, and W: 10-25%.

[0006] Preferably, the atomic percentages of the components of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film are: Ni: 22%, Ti: 14.1%, Ta: 18%, Mo: 16.6%, Nb: 13%, and W: 16.2%.

[0007] Preferably, the multi-level nanostructured NiTiTaMoNbW high entropy alloy film comprises a recrystallized layer, and the thickness of the recrystallized layer is 0.6-2 μm.

[0008] Preferably, when the volume percentage of the crystal phase of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film is 30%, the yield strength is 6.7 GPa; when the volume percentage of the crystal phase of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film is 40%, the elastic strain value is 8.5%.

[0009] The second aspect of the present application provides a method for regulating the mechanical properties of a multi-level nanostructured NiTiTaMoNbW high entropy alloy film of the first aspect of the present application, comprising: preparing a NiTiTaMoNbW high entropy alloy film; performing laser annealing on the NiTiTaMoNbW high entropy alloy film to form a recrystallization layer to change the crystal phase volume ratio of the high entropy alloy film.

[0010] Preferably, the method for preparing the NiTiTaMoNbW high entropy alloy film comprises: providing a single crystal silicon substrate, a TaMoNbW alloy target and a NiTi alloy target; co-sputtering the TaMoNbW alloy target and the NiTi alloy target onto the single crystal silicon substrate by radio frequency magnetron sputtering to obtain a NiTiTaMoNbW high entropy alloy film; the atomic percentages of the components of the TaMoNbW alloy target are the same, and the atomic percentages of the components of the NiTi alloy target are: Ni: 50.8%, Ti: 49.2%.

[0011] Preferably, the method for preparing the NiTiTaMoNbW high entropy alloy film comprises the following steps: (1) polishing a single crystal silicon substrate; (2) placing the polished single crystal silicon substrate, TaMoNbW alloy target and NiTi alloy target in a vacuum chamber, placing the TaMoNbW alloy target and NiTi alloy target on a DC cathode, closing the vacuum chamber, evacuating the chamber and heating the chamber; (3) introducing an inert gas into the vacuum chamber and performing magnetron sputtering to obtain a NiTiTaMoNbW high entropy alloy film.

[0012] Preferably, the pressure of the vacuum chamber after evacuation in (2) is less than 5.0×10 -3 Pa, the heating temperature is 300°C; in (3), the inert gas is introduced into the vacuum chamber until the pressure is 0.2Pa, the magnetron sputtering deposition power of the TaMoNbW alloy target is 100-200W, and the magnetron sputtering deposition power of the NiTi alloy target is 50-100W.

[0013] Preferably, the step of laser annealing the NiTiTaMoNbW high entropy alloy film comprises: irradiating the surface of the high entropy alloy film with a laser, and then cooling it to room temperature.

[0014] Preferably, the spot diameter of the laser is 10-100 μm, the scanning speed is 100-1000 mm / s, and the power is 0.33-3W.

[0015] Beneficial effects of the present application: Based on the preparation of a nearly equiatomic NiTiTaMoNbW high entropy alloy film, the present application processes the NiTiTaMoNbW high entropy alloy film by laser annealing to adjust the volume percentage of the crystalline phase in the NiTiTaMoNbW high entropy alloy film, thereby obtaining a NiTiTaMoNbW high entropy alloy film with a multi-level nanostructure, whose yield strength and elastic strain are higher than those of existing high entropy alloy films, and can simultaneously meet the requirements of high strength and high ductility. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for describing the embodiments.

[0017] Figure 1 A schematic diagram of a method for preparing a NiTiTaMoNbW high entropy alloy thin film provided in an embodiment of the present application;

[0018] Figure 2 A schematic diagram of a method for regulating the mechanical properties of a multi-level nanostructured NiTiTaMoNbW high entropy alloy film provided in an embodiment of the present application;

[0019] Figure 3 Microstructure analysis diagram of NiTiTaMoNbW high entropy alloy film provided in the embodiment of the present application:

[0020] (a) is a cross-sectional observation of a NiTiTaMoNbW high entropy alloy film; (b)-(g) are element spectra of Ta, Mo, Nb, W, Ni and Ti, respectively;

[0021] Figure 4 Microstructure analysis diagram of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 2 provided in the present application:

[0022] (a) is a cross-sectional observation of a multi-level nanostructured NiTiTaMoNbW high entropy alloy film; (b) and (c) are partial enlarged views of (a); (d), (e), and (f) are selected area electron diffraction analysis views of regions d, e, and f in (a), respectively;

[0023] Figure 5 Microstructure analysis diagram of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 3 provided in the present application:

[0024] (a) is a cross-sectional observation of a multi-level nanostructured NiTiTaMoNbW high entropy alloy film; (b) and (c) are partial enlarged views of (a); (d), (e), and (f) are selected area electron diffraction analysis views of regions d, e, and f in (a), respectively;

[0025] Figure 6 Microstructure analysis diagram of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 4 provided in the present application:

[0026] (a) is a cross-sectional observation of a multi-level nanostructured NiTiTaMoNbW high entropy alloy film; (b) and (c) are partial enlarged views of (a); (d), (e), and (f) are selected area electron diffraction analysis views of regions d, e, and f in (a), respectively;

[0027] Figure 7 Compression test diagram of in-situ microcolumns prepared with the NiTiTaMoNbW high entropy alloy film of Example 1 provided in the examples of the present application:

[0028] (a) The strain rate is 5×10 -4 s -1 Stress-strain curve; (b) is the SEM image of the microcolumn before compression, taken at an angle of 75° relative to the normal direction of the sample surface; (c)-(e) are SEM images of the microcolumns at strain (ε) levels of 6.1%, 10.3% and 13.4%, respectively; (f) is the SEM image of the microcolumn after compression test;

[0029] Figure 8 Compression test diagram of in-situ microcolumns prepared with the multi-level nanostructured NiTiTaMoNbW high entropy alloy film of Example 2 provided in the embodiments of the present application:

[0030] (a) The strain rate is 5×10 -4 s -1 Stress-strain curve; (b) is the SEM image of the microcolumn before compression, taken at an angle of 75° relative to the normal direction of the sample surface; (c)-(e) are SEM images of the microcolumn at strain (ε) levels of 20%, 25%, and 35%, respectively; (f) is the SEM image of the microcolumn after compression test;

[0031] Fig. 9 Compression test diagram of in-situ microcolumns prepared with the multi-level nanostructured NiTiTaMoNbW high entropy alloy film of Example 3 provided in the embodiments of the present application:

[0032] (a) The strain rate is 5×10 -4 s -1Stress-strain curve; (b) is the SEM image of the microcolumn before compression, taken at an angle of 75° relative to the normal direction of the sample surface; (c)-(e) are SEM images of the microcolumn at strain (ε) levels of 20%, 25%, and 42%, respectively; (f) is the SEM image of the microcolumn after compression test;

[0033] Fig.10 Compression test diagram of in-situ microcolumns prepared with the multi-level nanostructured NiTiTaMoNbW high entropy alloy film of Example 4 provided in the embodiments of the present application:

[0034] (a) The strain rate is 5×10 -4 s -1 Stress-strain curve; (b) is the SEM image of the microcolumn before compression, taken at an angle of 75° relative to the normal direction of the sample surface; (c)-(e) are SEM images of the microcolumn at strain (ε) levels of 20%, 25%, and 42%, respectively; (f) is the SEM image of the microcolumn after compression test;

[0035] Fig.11 The relationship diagram of the yield strength and elastic strain when the volume percentage of the crystal phase of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film provided in the embodiment of the present application changes:

[0036] (a) is the change of yield strength with the volume percentage of crystalline phase; (b) is the change of elastic strain with the volume percentage of crystalline phase;

[0037] Fig.12 This is a comparison chart of the yield strength and elastic strain of the NiTiTaMoNbW high entropy alloy film and the multi-level nanostructured NiTiTaMoNbW high entropy alloy film provided in the embodiments of the present application and the existing high entropy alloy film materials. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings and embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present application. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0039] It should be noted that if there are descriptions involving "first", "second", etc. in the implementation of this application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance and implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the fact that ordinary technicians in the field can implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0040] An embodiment of the present application provides a high entropy alloy film, which is a NiTiTaMoNbW alloy. The atomic percentages of the components of the NiTiTaMoNbW high entropy alloy film are: Ni: 10-25%, Ti: 10-25%, Ta: 10-25%, Mo: 10-25%, Nb: 10-25%, and W: 10-25%.

[0041] In some embodiments, the atomic percentages of the components of the NiTiTaMoNbW high entropy alloy film are: Ni: 22%, Ti: 14.1%, Ta: 18%, Mo: 16.6%, Nb: 13%, and W: 16.2%.

[0042] See also Figure 1 The present application also provides a method for preparing the NiTiTaMoNbW high entropy alloy film as described above, comprising: providing a single crystal silicon substrate, a TaMoNbW alloy target and a NiTi alloy target; co-sputtering the TaMoNbW alloy target and the NiTi alloy target onto the single crystal silicon substrate by radio frequency magnetron sputtering to obtain a high entropy alloy film. The atomic percentages of the components of the TaMoNbW alloy target are the same, and the atomic percentages of the components of the NiTi alloy target are: Ni: 50.8%, Ti: 49.2%. The growth rate of the high entropy alloy is about The final thickness was 5.33 μm.

[0043] In some embodiments, the method for preparing a NiTiTaMoNbW high entropy alloy thin film comprises the steps of:

[0044] (1) polishing the single crystal silicon substrate;

[0045] (2) placing the polished single crystal silicon substrate, TaMoNbW alloy target and NiTi alloy target in a vacuum chamber, with both the TaMoNbW alloy target and the NiTi alloy target placed on a DC cathode, closing the vacuum chamber, evacuating the chamber and heating the chamber;

[0046] (3) Inert gas is introduced into the vacuum chamber and magnetron sputtering is performed to obtain a high entropy alloy film.

[0047] Furthermore, after the vacuum is evacuated in (2), the pressure of the vacuum chamber is less than 5.0×10 -3 Pa, the heating temperature is 300° C.; (3) inert gas is introduced until the pressure in the vacuum chamber is 0.2 Pa, the magnetron sputtering deposition power of the TaMoNbW alloy target is 100-200 W, for example, the magnetron sputtering deposition power of the TaMoNbW alloy target is 100 W, 110 W, 120 W, 130 W, 140 W, 150 W, 160 W, 170 W, 180 W, 190 W or 200 W, etc. The magnetron sputtering deposition power of the NiTi alloy target is 50-100 W, for example, the magnetron sputtering deposition power of the NiTi alloy target is 50 W, 60 W, 70 W, 80 W, 90 W or 100 W, etc., and the inert gas can be argon.

[0048] The embodiment of the present application also provides a multi-level nanostructured NiTiTaMoNbW high entropy alloy film. The material of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film is NiTiTaMoNbW alloy. The atomic percentages of the components of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film are: Ni: 10-25%, Ti: 10-25%, Ta: 10-25%, Mo: 10-25%, Nb: 10-25%, and W: 10-25%.

[0049] In some embodiments, the atomic percentages of the components of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film are: Ni: 22%, Ti: 14.1%, Ta: 18%, Mo: 16.6%, Nb: 13%, and W: 16.2%.

[0050] In some embodiments, the multi-level nanostructured NiTiTaMoNbW high entropy alloy film includes a recrystallization layer, and the thickness of the recrystallization layer is 0.6-2 μm, for example, the thickness of the recrystallization layer is 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm, etc.

[0051] In some embodiments, when the volume percentage of the crystal phase of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film is 30%, the yield strength is 6.7 GPa; when the volume percentage of the crystal phase of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film is 40%, the elastic strain value is 8.5%.

[0052] The present application also provides a method for controlling the mechanical properties of a multi-level nanostructured NiTiTaMoNbW high entropy alloy film. Figure 2As shown, including:

[0053] Preparation of NiTiTaMoNbW high entropy alloy thin films;

[0054] Laser annealing is performed on the NiTiTaMoNbW high entropy alloy film to form a recrystallization layer to change the crystal phase volume ratio of the high entropy alloy film. The NiTiTaMoNbW high entropy alloy film is selected from the NiTiTaMoNbW high entropy alloy film described above or is prepared by the method for preparing the NiTiTaMoNbW high entropy alloy film described above.

[0055] In some embodiments, the step of laser annealing specifically includes: irradiating the surface of the NiTiTaMoNbW high entropy alloy film with a laser, and then cooling to room temperature. Wherein, the spot diameter of the laser is 10-100 μm, for example, the spot diameter of the laser is 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, etc. The scanning speed of the laser is 100-1000 mm / s, for example, the scanning speed of the laser is 100 mm / s, 200 mm / s, 300 mm / s, 400 mm / s, 500 mm / s, 600 mm / s, 700 mm / s, 800 mm / s, 900 mm / s or 1000 mm / s, etc. The power of the laser is 0.33-3 W, for example, the power of the laser is 0.33 W, 0.5 W, 1 W, 1.3 W, 1.5 W, 2 W, 2.5 W or 3 W, etc. Cooling can be performed by air cooling.

[0056] During laser annealing, the concentrated energy of the laser beam induces local melting and rapid solidification in the surface region of the NiTiTaMoNbW high-entropy alloy film. This phenomenon is attributed to the extremely high heating rate that can be achieved with laser processing. When the molten area solidifies, the rapid quenching prevents the formation of a complete crystalline structure, resulting in the formation of an amorphous phase in the substrate. In contrast, the surface region has a longer time for crystal growth, resulting in the formation of nanograins. This dual-phase structure is a direct result of the different cooling rates experienced by the surface and substrate regions.

[0057] Furthermore, the multi-level nanostructure produced by laser annealing has an impact on the mechanical and functional properties of NiTiTaMoNbW high-entropy alloy films. The coexistence of crystalline and amorphous phases gives the material unique properties, such as increased ductility and toughness. This can be attributed to the role of the amorphous phase region in energy dissipation during mechanical deformation, which effectively improves the film's resistance to fracture. In addition, the surface nanograins may promote mechanisms such as dislocation slip and twinning, further enhancing the film's mechanical response.

[0058] The following is further described through specific implementation methods.

[0059] Example 1

[0060] The single crystal silicon substrate was polished to form a mirror surface. The polished single crystal silicon substrate, TaMoNbW alloy target (equiatomic ratio), and NiTi alloy target (Ni: 50.8%, Ti: 49.2%) were placed in a vacuum chamber of a radio frequency magnetron sputtering device. The TaMoNbW alloy target and the NiTi alloy target were placed on a DC cathode, and the vacuum chamber was closed and evacuated to a pressure of less than 5.0×10 -3 Pa, and heated to 300° C. Then, argon gas was introduced into the vacuum chamber until the pressure was 0.2 Pa, and RF magnetron sputtering was started, and the magnetron sputtering deposition power of the TaMoNbW alloy target was set to 140 W, and the magnetron sputtering deposition power of the NiTi alloy target was set to 70 W, to obtain a NiTiTaMoNbW high entropy alloy film.

[0061] A focused ion beam (FIB, Helios NanoLabTM 600i, FEI, USA) was used to prepare cross-sectional TEM samples, and a transmission microscope (FEI Talos 200X) was used to observe the cross-sections. N The prepared NiTiTaMoNbW high entropy alloy film was analyzed by a silicon drift EDX detector (Oxford Instruments, UK), and the results are shown in Figure 3. Figure 3 In (a)-(g), it can be found that the thickness of the NiTiTaMoNbW high entropy alloy film is about 5.33 μm, which contains 22.0% Ni, 14.1% Ti, 18.0% Ta, 16.6% Mo, 13.0% Nb and 16.2% W, which is nearly equiatomic.

[0062] Embodiment 2-4

[0063] The NiTiTaMoNbW high entropy alloy film prepared in Example 1 was subjected to laser annealing treatment according to the parameters in Table 1 to obtain a multi-level nanostructured NiTiTaMoNbW high entropy alloy film.

[0064] Table 1 Laser annealing parameters

[0065] Laser power W Laser scanning speed mm / s coating Spot diameter μm Example 2 0.33 100 Black paint 50 Example 3 1 100 Black paint 50 Example 4 3 100 Black paint 50

[0066] Test Example 1

[0067] (1) The microstructure of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 2 was observed. A cross-sectional TEM sample was prepared using a focused ion beam (FIB, Helios NanoLabTM 600i, FEI, USA), and the cross section was observed using a transmission microscope (FEI Talos 200X). The results are shown in Figure 2. Figure 4 As shown in (a), from Figure 4 As can be seen in (a), there is an obvious recrystallization layer on the surface of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 2, with a thickness of about 641 nm. Figure 4 As shown in (b) and (c), the grain size is found to be about 20 nm. Figure 4 The selected d area, e area and f area of ​​(a) were subjected to selected area electron diffraction analysis, and the results were as follows: Figure 4 As shown in (d), (e) and (f). Figure 4 It can be seen from (d), (e), and (f) that there are crystalline phases and amorphous phases in region d, indicating that the amorphous phase has not been completely recrystallized. A similar phenomenon can be observed in region e. Region f is all amorphous phase, indicating that it is not affected by laser annealing.

[0068] (2) The microstructure of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 3 was observed. The cross-sectional observation results were as follows: Figure 5 As shown in (a), from Figure 5 As can be seen in (a), there is an obvious recrystallization layer on the surface of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 3, with a thickness of about 701 nm. Figure 5 As shown in (b) and (c), the grain size is found to be about 20 nm. Figure 5 The selected d area, e area and f area of ​​(a) were subjected to selected area electron diffraction analysis, and the results were as follows: Figure 5 As shown in (d), (e) and (f). Figure 5 It can be seen from (d), (e), and (f) that there are crystalline phases and amorphous phases in region d, indicating that the amorphous phase has not been completely recrystallized. A similar phenomenon can be observed in region e. Region f is all amorphous phase, indicating that it is not affected by laser annealing.

[0069] (3) The microstructure of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 4 was observed. The cross-sectional observation results were as follows: Figure 6 As shown in (a), from Figure 6As can be seen in (a), there is an obvious recrystallization layer on the surface of the multi-level nanostructured high entropy alloy film prepared in Example 4, with a thickness of about 1.4 μm. Figure 6 As shown in (b) and (c), the grain size is found to be about 20 nm. Figure 6 The selected d area, e area and f area of ​​(a) were subjected to selected area electron diffraction analysis, and the results were as follows: Figure 6 As shown in (d), (e) and (f). Figure 6 It can be seen from (d), (e), and (f) that the region d mainly contains crystalline phases, indicating that the amorphous phase is almost completely recrystallized. The region e contains crystalline phases and amorphous phases, indicating that the amorphous phase is not completely recrystallized. The region f is entirely amorphous phase, indicating that it is not affected by laser annealing.

[0070] Test Example 2

[0071] Rectangular micropillars (1×1×2 μm) were prepared on the polished surface of the NiTiTaMoNbW high entropy alloy film with multi-level nanostructures prepared in Example 2-4 using a focused ion beam (FIB) in a Helios G4 dual beam system (Thermo Fisher Scientific). 3 In situ micropillar compression tests were performed in a TESCAN MIRA 3 SEM using a FemtoTools nanomechanical testing system (model FT-NMT04, Buchs ZH, Switzerland) equipped with a 5 μm diameter diamond flat punch. Force-displacement data were collected via piezoelectric actuators in capacitive sensors. Real-time video recordings of the morphological evolution of the micropillars during compression were performed. All micropillars were compressed in displacement-controlled mode to a strain of approximately 50% and then unloaded. A constant strain rate was used for all experiments. 5×10 -4 s -1 .

[0072] (1) The stress-strain curve of the NiTiTaMoNbW high entropy alloy film prepared in Example 1 was tested. The results are shown in Figure 7 As shown in (a)-(f), combined Figure 7 As can be seen from (a)-(f), the stress-strain curve first shows linear elastic deformation behavior and drops at a strain level of about 6.1% and a stress level of about 6610MPa. Then, the stress-strain curve continues to show strain hardening behavior, with several small drops during the strain hardening process. It can be seen that the top area of ​​the microcolumn prepared with the NiTiTaMoNbW high entropy alloy film prepared in Example 1 slips and expands to several parts.

[0073] (2) The stress-strain curve of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 2 was tested. The results are shown in Figure 8 As shown in (a)-(f), combined Figure 8 As can be seen in (a)-(f), the stress-strain curve first shows linear elastic deformation behavior and drops at a strain level of about 20% and a stress level of about 5800 MPa. Then, the stress-strain curve continues to show strain hardening behavior, with several small drops during the strain hardening process. It can be seen that the micropillars prepared with the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 2 show a fracture mode caused by shear in the bottom region, which may be caused by surface recrystallization and an increase in surface plasticity.

[0074] (3) The stress-strain curve of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 3 was tested. Fig. 9 As shown in (a)-(f), combined Fig. 9 As can be seen from (a)-(f), the stress-strain curve first shows linear elastic deformation behavior and drops at a strain level of about 20% and a stress level of about 6 GPa. Then, the stress-strain curve continues to show strain hardening behavior, with several small drops during the strain hardening process. It can be seen that the micropillars prepared with the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 3 show a fracture mode caused by shear in the bottom region, which may be caused by surface recrystallization and an increase in surface plasticity.

[0075] (4) The stress-strain curve of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 4 was tested. Fig.10 As shown in (a)-(f), combined Fig.10 As can be seen from (a)-(f), the stress-strain curve first shows linear elastic deformation behavior and drops at a strain level of about 18% and a stress level of about 5.2 GPa. Then, the stress-strain curve continues to show strain hardening behavior, with several small drops during the strain hardening process. It can be seen that the micropillars prepared with the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Example 3 show a fracture mode caused by shear in the bottom region, which may be caused by surface recrystallization and an increase in surface plasticity.

[0076] (5) Combining the test results of (2), (3) and (4), the relationship between the yield strength and elastic strain of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film when the volume percentage of the crystal phase changes can be obtained, such as Fig.10 As shown. Fig.11As can be seen in (a), the yield strength first increases and then decreases with the volume percentage. When the volume percentage reaches about 30%, the yield strength reaches a maximum value of 6.7 GPa. Fig.11 As can be seen in (b), the elastic strain first increases and then decreases with the volume percentage. When the volume percentage reaches about 40%, the elastic strain reaches a maximum value of 8.5%.

[0077] Test Example 3

[0078] The yield strength and elastic strain of the NiTiTaMoNbW high entropy alloy film prepared in Example 1 and the multi-level nanostructured NiTiTaMoNbW high entropy alloy film prepared in Examples 2-4 were compared with the existing high entropy alloy films. Fig.12 As shown. Fig.12 It can be seen that the yield strength and elastic strain of the NiTiTaMoNbW high entropy alloy film and the multi-level nanostructured NiTiTaMoNbW high entropy alloy film in the embodiments of the present application are higher than those of the existing high entropy alloy films.

[0079] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.

Claims

1. A multi-level nanostructured NiTiTaMoNbW high entropy alloy film, characterized in that: The multi-level nanostructured NiTiTaMoNbW high entropy alloy film material is NiTiTaMoNbW alloy, and the atomic percentages of the components of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film are: Ni: 10-25%, Ti: 10-25%, Ta: 10-25%, Mo: 10-25%, Nb: 10-25%, and W: 10-25%.

2. The multi-level nanostructured NiTiTaMoNbW high entropy alloy film according to claim 1, characterized in that: The atomic percentages of the components of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film are: Ni: 22%, Ti: 14.1%, Ta: 18%, Mo: 16.6%, Nb: 13%, and W: 16.2%.

3. The multi-level nanostructured NiTiTaMoNbW high entropy alloy film according to claim 1, characterized in that: The multi-level nanostructured NiTiTaMoNbW high entropy alloy film comprises a recrystallized layer, and the thickness of the recrystallized layer is 0.6-2 μm.

4. The multi-level nanostructured NiTiTaMoNbW high entropy alloy film according to claim 1, characterized in that: When the volume percentage of the crystal phase of the multi-level nanostructured NiTiTaMoNbW high entropy alloy film is 30%, the yield strength is 6.7 GPa; When the volume percentage of the crystal phase of the multi-level nanostructured high entropy alloy film is 40%, the elastic strain value is 8.5%.

5. A method for controlling the mechanical properties of a multi-level nanostructured NiTiTaMoNbW high entropy alloy film according to any one of claims 1 to 4, characterized in that: include: Preparation of NiTiTaMoNbW high entropy alloy thin films; Laser annealing is performed on the NiTiTaMoNbW high entropy alloy film to form a recrystallization layer so as to change the crystal phase volume ratio of the high entropy alloy film.

6. The method according to claim 5, characterized in that The preparation method of the NiTiTaMoNbW high entropy alloy film comprises: Providing a single crystal silicon substrate, a TaMoNbW alloy target and a NiTi alloy target; co-sputtering the TaMoNbW alloy target and the NiTi alloy target onto the single crystal silicon substrate by radio frequency magnetron sputtering to obtain a NiTiTaMoNbW high entropy alloy film; The atomic percentages of the components of the TaMoNbW alloy target are the same, and the atomic percentages of the components of the NiTi alloy target are: Ni: 50.8%, Ti: 49.2%.

7. The method according to claim 6, characterized in that The method for preparing the NiTiTaMoNbW high entropy alloy film comprises the steps of: (1) polishing the single crystal silicon substrate; (2) placing the polished single crystal silicon substrate, TaMoNbW alloy target and NiTi alloy target in a vacuum chamber, with both the TaMoNbW alloy target and the NiTi alloy target placed on a DC cathode, closing the vacuum chamber, evacuating the chamber and heating the chamber; (3) Inert gas is introduced into the vacuum chamber and magnetron sputtering is performed to obtain a NiTiTaMoNbW high entropy alloy film.

8. The method according to claim 7, characterized in that After the vacuum is evacuated in (2), the pressure of the vacuum chamber is less than 5.0×10 -3 Pa, heating temperature is 300℃; In the step (3), an inert gas is introduced into the vacuum chamber until the pressure is 0.2 Pa. The magnetron sputtering deposition power of the TaMoNbW alloy target is 100-200 W, and the magnetron sputtering deposition power of the NiTi alloy target is 50-100 W.

9. The method according to claim 5, characterized in that The step of laser annealing the NiTiTaMoNbW high entropy alloy film is: irradiating the surface of the NiTiTaMoNbW high entropy alloy film with a laser, and then cooling it to room temperature.

10. The method according to claim 9, characterized in that The spot diameter of the laser is 10-100 μm, the scanning speed is 100-1000 mm / s, and the power is 0.33-3W.

Citation Information

Cited By

  • Ti-Zr-Hf-Co-Ni-Cu high-entropy metal glass film with low roughness and high strain rate sensitivity and preparation method

    CN122484690A